Science Teachers’ Opinions on Application of Competency-Based Science Model Components to Science Programs - Suleyman Yaman (International Journal of Evaluation and Research in Education (IJERE), 2017)
The aim of this study is to reveal the opinions of teachers, who gave the science lessons that took effect in Turkey in 2004 and 2013, on the sub-components of the programs and to identify to what extent the objectives of the program have been achieved. In total 89 teachers, out of which 42 were females and 47 were males, in the study which was conducted by the semi-structured interview method. Data collected from the study, where five questions were asked to teachers, was settled by analyzing the science programs according to components of the Ohio Competency Based Science Model. While result from the study shows that the teachers were qualified to ensure the development of some behaviors that were expected to be seen on the students as a result of science programs; especially the students gave a lower level of positive opinion about the components related with how they will use this data. In addition; while the teachers supported that the scientific process skills, are one of the basic elements of science programs, were sufficient for the gain of basic skills, they stated that they are not sufficient for the gain of some causal and experimental skills.